Technology enhancement learning reflection on improving students’ satisfaction in Omani Universities - Tawafak, Ragad M.; Mohammed, Muamer N.; Ruzaini, Abdullah Arshah; Shakir, Mohanaad; Mezhuyev, Vitaliy (Publishing Technology, 2018)
The excellence of Omani Universities in technology enhancement learning (TEL) has become essential in supporting the rapid growth and sustainability of the education sector for usage and application. Technology enhancement learning is depending on use of different application tools like Microsoft office files and video blog programs to facilitate the academic performance. The real problem faced education is a need for several applications and technologies in the higher education institutions in Oman to improve their outputs and improve on teacher-student satisfaction. This paper aims to determine the common type of (TEL) of video and attached assignments and data analysis used in the Universities. In addition to facilitate (TEL) used is used in colleges and Universities in conjunction with improving lab equipment and administrative systems. In the first phase of this study, a systematic review of the existing literature was carried out to determine and define the suitable quantitative and qualitative criteria of existence applications; and then, design and exploit pair-wise comparison and online evaluation forms to get experts opinions/preference on the evaluation criteria used to measure the satisfaction of these technologies. In this study, survey questionnaires were distributed to 3 different Universities in Oman to assess their technology enhancement learning performances which served as a link between the Universities and higher education (HEI). The findings of this paper aid in establishing the need to improve teaching material by using attached assignment with material description by video programs in the Universities, higher educational institutions (HEI); and new techniques that add value in teacher assessment method for student satisfaction in higher education. Further studies could be carried out in the future with more technological developments.